Philosophy for architects. - Mitrovic, Branko, ....- (New York : Princeton Architectural Press, 2011)
Philosophy for Architects Branko Mitrovi Philosophy for Architects is an engaging and easy-to-grasp introduction to philosophical questions of interest to students of architectural theory. Topics include Aristotle's theories of "visual imagination" and their relevance to digital design, the problem of optical correction as explored by Plato, Hegel's theory of zeitgeist, and Kant's examinations of space and aesthetics, among others. Focusing primarily on nineteenth- and twentieth-century philosophy, it provides students with a wider perspective concerning philosophical problems that come up in contemporary architectural debates.
Keywords: Architectuur; Wonen -- Filosofie